Boundaries of the Human in the Contemporary Post-Apocalyptic Novel: McCarthy and Houellebecq. - Valentino Baldi (Between, 2015)
This paper focuses on the analysis of Houellebecq’s La possibilité d’une île and McCarthy’s The Road with the objective to trace how the representation of the human changes in the contemporary post-apocalyptic novel. The article is based on references to the theories of Agamben, Bauman and Žižek and it develops an idea of literature as return of the repressed theorised by Francesco Orlando.